PENGARUH KECERDASAN SPIRITUAL DAN FAKTOR-FAKTOR LAINNYA TERHADAP PRODUKTIVITAS TENAGA KERJA PADA USAHATANI JAGUNG DI KAWASAN AGROPOLITAN KABUPATEN CIAMIS - Amalia, Lidya Nur (Universitas Galuh, 2023)
Labor as a factor of production affects production costs where an increase in labor productivity can lead to higher production. The purpose of this study was to determine the influence of spiritual intelligence and other factors on labor productivity in corn farming in the agropolitan area of Ciamis Regency. The research was carried out using a quantitative research approach. A sample of 94 people was obtained from a population of 1,545 corn farmers using the Slovin formula. The influence of spiritual intelligence and other factors on the productivity of corn farming in the agropolitan area of Ciamis Regency was analyzed using multiple linear regression. The results showed that land area, family size, and spiritual intelligence had a significant effect on the labor productivity of corn farming in the agropolitan area of Ciamis Regency; while education and experience have no significant effect.